THE INFLUENCE OF HEDONIC SHOPPING VALUE ON INTERESTED IN BUYING DISCOUNTED PRODUCTS (Case Study of Isano Collection Lhokseumawe Store) - Nadia Fajri; Siti Maimunah; Heriyana; Halida Bahri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to see the influence of hedonic shopping value on interest in buying discount products (Case Study of the Isano Collection Lhokseumawe Store). The sampling technique in this research is accidental sampling. The sample in this research was 120 consumers who purchased at the Toko Isano Collection Lhokseumawe store. The analytical tools used are multiple linear regression tests and hypothesis testing using the t test and F test. The results of the research show that partially the variables Novelty, Enjoyment, Social Interaction have a positive and significant influence on Purchase Interest at the Isano Collection Lhokseumawe Store. Meanwhile, the variables Praise from other people and escape have no effect on buying interest at the Isano Collection Lhokseumawe Shop. The variables Novelty, Enjoyment, Social Interaction, Praise from others and escape have a positive and significant effect on Purchase Interest at the Isano Collection Lhokseumawe Store.